ChemInform Abstract: Facile Synthesis of Novel Halogenated 4‐Pyrazolylspirocyclic‐β‐lactams: Versatile Heterocyclic Synthons. Issue 41 (September 2016) - Bhalla, Aman; Bari, Shamsher S.; Bhalla, Jitender; Khullar, Sadhika; Mandal, Sanjay
Abstract: The synthesis of the title species (IV) is based on iodine mediated intrasulfenyl cyclization of precursors (III).